Embodied Thinking in the Practice of Qualitative Inquiry - Armanto (SAGE, 2025)
With this mixed media collage I explore embodiment in the practice of qualitative inquiry. In my doctoral research, I study anticipation in climate-wise farming and sometimes I tend to struggle with Words. Writing about someone else’s futures is a delicate matter and the feelings of getting nowhere often embrace me. As I am sitting in front of my desk, staring outside of the window, trying to conceive how, (and sometimes why), I see the coniferous green, typical Finnish forest growing around our house. There is a need for me to get out, to come and go. I need to re-work the pattern of working as typing with stillness. To have a move and a movement to extend what can be thought as researching. What can be thought as working? Could I wander-around-wonder? I put on my rubber boots and went outside, looking for mushrooms. The first modest attempt to somehow let myself to be immersed rapidly flourished into joyfully thinking with the forest. I was what I found, the embodied personal anticipations right there in the existence and the golden yellow chantarelle (Cantharellus cibarius) popping through the mass of moss like insights. It felt right. So, this piece emerged from the need to do differently. It works as an opening to the process of thinking with movement, to allow and appreciate bodily acts (more-than-typing) as integral to thinking and writing science. What is it to think with drawing, handwriting, walking, ice swimming, visualizing, watching skateboarders, with the forest, on the road, in the airport? Creating the collage of layered materials with my sister auto-manifests that thinking with is dynamic, and I keep on moving to stay again. With my acts I anticipate, and become as what I already am.